2020
DOI: 10.1038/s41598-020-66182-8
|View full text |Cite
|
Sign up to set email alerts
|

Elbasvir/grazoprevir for hepatitis C virus genotype 1b East-Asian patients receiving hemodialysis

Abstract: In conclusion, our multicenter prospective study confirms that EBR/GZR for 12 weeks is effective for East-Asian HCV GT1b patients receiving hemodialysis. Furthermore, the tolerability is also excellent for these patients receiving EBR/GZR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Across 3817 patients, only 35 were on peritoneal dialysis. 9 , 22 , 23 , 24 , 26 , 29 , 30 , 31 , 34 , 37 , 38 , 39 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 The s...…”
Section: Ckd G4–g5ndunclassified
“…Across 3817 patients, only 35 were on peritoneal dialysis. 9 , 22 , 23 , 24 , 26 , 29 , 30 , 31 , 34 , 37 , 38 , 39 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 The s...…”
Section: Ckd G4–g5ndunclassified
“…Telcagepant is in a clinical phase 3 trial for acute migraine [ 89 ], but it is not yet under the clinical phase for COVID-19. Elbasvir is an FDA-approved drug for the treatment of hepatitis C virus genotype 1b (HCV GT1b) patients [ 90 ], and it is supported for COVID-19 by other studies [ 91 ], but is not yet considered for a clinical trial for COVID-19. To compare our suggested eight drug molecules against the two FDA-approved drugs (Molnupiravir and Nirmatrelvir) for COVID-19, we investigated their docking scores (kcal/mol) with our proposed and top-ranked published target proteins and found that our proposed drug molecules produced higher binding affinity scores in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…One major limitation of the information reported above is that it is mostly based on industry-funded studies, and these kinds of studies are more likely to be published if results are favourable [30]. However, numerous real-life studies on the same point have been completed supporting the conclusions reported above [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Pi-containing Sof-free Daas (Real World Studies)mentioning
confidence: 99%